2007
DOI: 10.1111/j.1538-7836.2007.02524.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the ‘4Ts’ score and particle gel immunoassay specific to heparin/PF4 for the diagnosis of heparin‐induced thrombocytopenia

Abstract: To cite this article: Pouplard C, Gueret P, Fouassier M, Ternisien C, Trossaert M, Ré gina S, Gruel Y. Prospective evaluation of the Ô4TsÕ score and particle gel immunoassay specific to heparin/PF4 for the diagnosis of heparin-induced thrombocytopenia. J Thromb Haemost 2007; 5: 1373-9.See also Arnold DM, Kelton JG. Testing for heparin-induced thrombocytopenia: are we there yet? This issue, pp 1371-2.Summary. Background: Heparin-induced thrombocytopenia (HIT) is a severe disease that is often difficult to diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
178
1
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(200 citation statements)
references
References 32 publications
18
178
1
3
Order By: Relevance
“…30 The positive predictive value of the 4Ts score was as low as 15.4%, a value less than the previously reported range from 21.4% to 100%. [8][9][10]15,[22][23][24][25][26] The false-positive rate of the 4Ts score (percentage of "4T high score" patients in the non-HIT patients) was 11.8%, a value comparable to those previously reported (0-15.3%). [8][9][10]15,[22][23][24][25][26] In contrast, the false-negative rate of the 4Ts scores (percentage of "4T low score" patients in HIT patients) was 54.5% (6/11), a value considerably higher than those previously reported (0-25%).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…30 The positive predictive value of the 4Ts score was as low as 15.4%, a value less than the previously reported range from 21.4% to 100%. [8][9][10]15,[22][23][24][25][26] The false-positive rate of the 4Ts score (percentage of "4T high score" patients in the non-HIT patients) was 11.8%, a value comparable to those previously reported (0-15.3%). [8][9][10]15,[22][23][24][25][26] In contrast, the false-negative rate of the 4Ts scores (percentage of "4T low score" patients in HIT patients) was 54.5% (6/11), a value considerably higher than those previously reported (0-25%).…”
Section: Discussionsupporting
confidence: 78%
“…[8][9][10]15,[22][23][24][25][26] The false-positive rate of the 4Ts score (percentage of "4T high score" patients in the non-HIT patients) was 11.8%, a value comparable to those previously reported (0-15.3%). [8][9][10]15,[22][23][24][25][26] In contrast, the false-negative rate of the 4Ts scores (percentage of "4T low score" patients in HIT patients) was 54.5% (6/11), a value considerably higher than those previously reported (0-25%). [8][9][10]15,[22][23][24][25][26] These findings suggested that many individuals might develop HIT even with a low 4Ts score.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Five studies evaluating a clinical score (4 Ts) [6][7][8][9][10] and three studies evaluating an IA were included [6,8,10]. In all of these studies but one [9], HIT was diagnosed if serotonin release was > 20% with 0.1 U mL )1 heparin and < 20%…”
mentioning
confidence: 99%